High school students’ justification to solve algebraic mathematics reasoning problems: Descriptive analysis from the nature of justification tasks - Razi, Fakhrur (Universitas Islam Negeri Raden Intan Lampung, 2024)
Justification serves as a tool used to improve students' ability to understand mathematics and their proficiency in working on mathematical problems. However, despite its significance, student justification in the problem-solving process has not become a priority for teachers based on several studies. While justification research related to problem-solving has begun to develop, it is only limited to validating the truth of a mathematical solution. Thus, this qualitative descriptive research aims to analyze students' justification process in solving reasoning problems regarding the types of justification (interpretation, elaboration, prediction, and validation) and the function of each type. The research subjects consisted of two high school students in Indonesia with high abilities who solved algebraic mathematics reasoning problems. Meanwhile, data collection and analysis used the results of students solving algebraic reasoning problems involving the nature of justification tasks. The results show that the types of justification indicate a crucial role in students' problem-solving process. Apart from that, each of these also has the potential for use in the problem-solving process. Furthermore, this article also suggests several points that can be applied to develop student justification in reasoning algebraic problems.